Mechanistic insights into the anti-cariogenic properties of theaflavins against streptococcus mutans: in silico - Fadhlina, Anis (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2024)
PURPOSE: This study aims to investigate the antibacterial mechanisms of theaflavins against S. mutans using in-silico methods. METHODS: PyRx version 0.8 was used to evaluate the binding affinities of four selected theaflavins (TF1, TF2a, TF2b, and TF3), against seven S. mutans proteins (PDB 4TQX: Sortase A, PDB 6CAM: Glucan binding protein, PDB 3QE5: Cell surface protein, PDB 3VX4: Quorum sensing, PDB 3AIC: Glucosyltransferase, PDB 2W3Z: Immune evasion, PDB 3CZC: Carbohydrate uptake). All the ligands were prepared and optimized using Avogadro-1.2 prior to the molecular docking. The Biovia Discovery visualizer was used to observe protein-ligand interactions. RESULTS: TF3 generally demonstrates the strongest binding affinity across most proteins, particularly against glucan binding protein and glucosyltransferase. CONCLUSION: Findings indicated that these theaflavins exhibit significant binding affinities to various S. mutans proteins, specifically TF3, suggesting their potential as anti-caries agents for therapeutic applications.